Magneto-transport properties of monolayer borophene in perpendicular magnetic field: influence of electron-phonon interaction - Ta T. Tho; T. Hoa Huynh; V. Chuong Nguyen; M. Tuan Luong; Dinh Hoi Bui (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên, 2022)
The magneto-transport properties of a borophene monolayer in a perpendicular magnetic field B are studied via calculating the conductivity tensor and resistance under electron-optical phonon interaction by using the linear response theory. Numerical results are obtained and discussed for some specific parameters. The magnetic field-dependent longitudinal conductivity shows the magneto-phonon resonance effect that describes the transition of electrons between Landau levels by absorbing/emitting an optical phonon. The Hall conductivity increases first and then decreases with the magnetic field strength. Also, the longitudinal resistance increases significantly with increasing temperature, which shows the metal behaviour of the material. Practically, the observed magneto-phonon resonance can be applied to experimentally determine some material parameters, such as the distance between Landau levels and the optical phonon energy.